Intervention of Entrepreneurship Values to Improve Entrepreneur Interest on Persons with Disabilities - Setiawan, Arozi; Yusuf, Munawir; Gunarhadi, Gunarhadi (The Center for Disability Studies and Services Brawijaya University, 2022)
This paper aims to know the entrepreneurship interest on the disabilities and the impacts of this entrepreneurship values intervention on their entrepreneur interest. Data is collected from standardized questionnaire of entrepreneurship interest including attention, interest, desire, decision and action with reliability level of 0.892. Data is analyzed on the normality, then using paired samples t-test to know the impacts of provided treatment. Results of this study show that (1) the intervention of entrepreneurship values can improve entrepreneur interest on the disabilities in Surakarta; (2) before treatment, the level of entrepreneur interest on the disabilities is in medium-to-low level with the percentage of 86.99%; (3) the level of entrepreneur interest after treatment is improving to percentage of 82.05%.